2011
DOI: 10.1021/ac201654r
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Measurement Technique for Ion Distribution in an Extended Nanochannel by Super-Resolution-Laser-Induced Fluorescence

Abstract: Ion behavior confined in extended nanospace (10(1)-10(3) nm) is important for nanofluidics and nanochemistry with dominant surface effects. In this paper, we developed a new measurement technique of ion distribution in the nanochannel by super-resolution-laser-induced fluorescence. Stimulated emission depletion microscopy was used to achieve a spatial resolution of 87 nm higher than the diffraction limit. Fluorescein was used for ratiometric measurement of pH with two excitation wavelengths. The pH profile in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 31 publications
2
68
0
Order By: Relevance
“…STED competes effectively with this nonradioactive decay, providing a new contrast mechanism which has been investigated in the vascular network of a nude mouse ear [241]. In addition, STED has been implemented in nanofluidic studies [242,243] with reported spatial resolutions better than 70 nm; and in protein flow cytometry research [244].…”
Section: Stimulated Emission Depletion Microscopymentioning
confidence: 99%
“…STED competes effectively with this nonradioactive decay, providing a new contrast mechanism which has been investigated in the vascular network of a nude mouse ear [241]. In addition, STED has been implemented in nanofluidic studies [242,243] with reported spatial resolutions better than 70 nm; and in protein flow cytometry research [244].…”
Section: Stimulated Emission Depletion Microscopymentioning
confidence: 99%
“…They found that the extended nanospace confinement resulted in a decrease of approximately one pH unit. Kazoe et al [28] investigated the distribution of proton concentrations in 2D extended nanochannels (410 nm) fabricated on fused silica glass by using STED (stimulated emission depletion) microscopy. The system is constructed by fluorescence excitation with a Gaussian intensity profile and STED beam with a doughnut-shaped intensity profile, and their beams are coaxially focused, with an objective lens to sample.…”
Section: Proton and Ion Transport Phenomena In Extended Nanospacesmentioning
confidence: 99%
“…[12,39] In addition, the experimentally obtained proton distribution of dilute solutions in extended nanospace is found to be inconsistent with the theoretically derived one. [28,40] Such discrepancies appear especially in sol- utions in which an excess number of protons exist, such as in dilute aqueous solutions and acid solutions. Accordingly, the establishment of a novel model, which is more appropriate for expressing unique liquid/proton behavior in extended nanospaces, is essential, while the EDL model provides one possible explanation for their behavior.…”
Section: Molecular Description Of the Liquid Phase In Extended Nanospmentioning
confidence: 99%
“…Although the STED laser narrows the focal spot, a depth-wise resolution determined by the focal depth is still under the optical diffraction limit. The STED microscopy was demonstrated for imaging of nanoparticles stuck on a glass surface to evaluate a spatial resolution [32]. A STED microscope was composed of Ar laser of 458 nm/488 nm wavelengths for the excitation, a fiber laser of 592 nm wavelength for STED, an oil immersion objective lens (100×, NA = 1.4, refractive index of immersion oil n = 1.52) and an avalanche photo diode (APD).…”
Section: Stimulated Emission Depletion Microscopymentioning
confidence: 99%